Faire ou défaire la frontière fluviale : penser et vivre l’Amou-Daria au x e siècle - Camille Rhoné (Frontière·s)
During the 10th century, the Amu Darya was part of the Islamic empire, then subject to the power of the Abbasid caliphate in the East. More than two centuries after the Arab-Muslim conquests, it still remains a frontier par excellence. This article aims to study the Amu Darya as both a thought and a lived frontier, in a context of political fragmentation within the Caliphate, in order to shed light on the diversity of relations of powers and populations with this river frontier, in a multi-scale approach. Far from being a peripheral zone, this river is fully integrated into traffic networks and marked by regional and supra-regional power relations. On the axes of the great Eurasian trade, the Amu Darya is a place where trade is concentrated. It represents a saving haven for travellers in a region largely marked by vast deserts both to the east and to the west, but it also gathers many material stakes, both fiscal and military. The neighbouring populations still appear to be mostly armed and characterized by a frontier mentality.